Purification and characterization of α-L-fucosidase from human primary hepatocarcinoma tissue - Li, Chao (Baishideng Publishing Group Co., Limited, 2006)
AIM: To purify and characterize α-L-fucosidase from human liver cancer tissue and to detect the localization of α-L-fucosidase in tumor tissue. METHODS: Cation exchange chromatography on CM-52 and ultrafiltration were used to separate α-L-fucosidase (AFU) from crude extract of liver cancer tissue. 4-methylumbelliferyl-α-L-fucopyranoside was used as a fluorescent substrate to quantify the purified AFU activity in each step. A polyclonal antibody (pAb) against the purified AFU was obtained by anion exchange chromatography on DEAE-52 after ammonium sulfate fractionation and ultrafiltration. Immuohistochemical staining was used to observe the expression of AFU in malignant and adjacent liver tissues. RESULTS: Human α-L-fucosidase was purified 74–fold to apparent homogeneity with 15% yield. SDS-PAGE indicated the presence of one subunit of molecular weight of 55 Ku. The specific activity of AFU in pooled fraction by chromatography was 10085 IU/mg. Western blot analysis indicated that the pAb could recognize one protein band of molecular weight of 55 Ku. The expression of AFU was observed in cytoplasm membrane of liver cancer tissue but not in that of adjacent tissue. CONCLUSION: The purified α-L-fucosidase from primary hepatocarcinoma (PHC) is different in its properties from α-L-fucosidase in human other organs. The polyclonal antibody prepared in this experiment can be applied to the diagnosis of PHC.